2000
DOI: 10.1209/epl/i2000-00334-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cluster formation on isospin asymmetry in the liquid-gas phase transition region

Abstract: Nuclear matter within the liquid-gas phase transition region is investigated in a mean-field two-component Fermi-gas model. Following largely analytic considerations, it is shown that: (1) Due to density dependence of asymmetry energy, some of the neutron excess from the high-density phase could be expelled into the low-density region. (2) Formation of clusters in the gas phase tends to counteract this trend, making the gas phase more liquid-like and reducing the asymmetry in the gas phase. Flow of asymmetry b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Given (N/Z) total and (N/Z) free , the (N/Z) bound is not unique but depends on how the total charge is shared between the two phases, i.e., the Z g /Z l factor. As discussed in detail in Chapter 5, essentially all thermal and dynamical models have predicted that the (N/Z) free is larger than the (N/Z) bound , and this phenomenon is generally known as the isospin fractionation [24,27,30,45,357,358,475,476]. Since (N/Z) free and (N/Z) bound are normally calculated by integrating over momentum, the above phenomenon is thus referred as the integrated isospin fractionation.…”
Section: Integrated Isospin Fractionation In Heavy-ion Reactionsmentioning
confidence: 99%
“…Given (N/Z) total and (N/Z) free , the (N/Z) bound is not unique but depends on how the total charge is shared between the two phases, i.e., the Z g /Z l factor. As discussed in detail in Chapter 5, essentially all thermal and dynamical models have predicted that the (N/Z) free is larger than the (N/Z) bound , and this phenomenon is generally known as the isospin fractionation [24,27,30,45,357,358,475,476]. Since (N/Z) free and (N/Z) bound are normally calculated by integrating over momentum, the above phenomenon is thus referred as the integrated isospin fractionation.…”
Section: Integrated Isospin Fractionation In Heavy-ion Reactionsmentioning
confidence: 99%
“…Then we calculated the gap voltages ͑V gap 's͒ at breakdown from the electrical measurement technique from the previous work of Massines et al 11 Figure 2 shows the change in the V gap at breakdown as a function of temperature, and in this figure, two interesting results were observed. 12 Nevertheless, because the pressure in the chamber was always maintained at 1 atm, the liquidlike phase transition causes an abrupt increases in the gas density. Theoretically, if the temperature is decreased under the same conditions, the gas density increases according to the equation of state.…”
mentioning
confidence: 99%
“…Previous authors have identified issues relevant to our calculations, which may influence the asymmetries of the hot fragments at freeze-out [45,49,50]. As discussed above, the present simulations underestimate the emission of light clusters (d, t, 3 He, 4 He, 6 Li, 7 Li, etc.)…”
Section: Discussion and Summarymentioning
confidence: 54%
“…during the dynamical evolution prior to the freeze-out. Previous studies [45,49,50] have noted that the neglect of the emission of 4 He emission is particularly problematic because it is abundant and because each 4 He particle enhances the isospin asymmetry of the remaining system by removing four nucleons without changing the neutron excess. Indeed, it has been speculated that 4 He emission may have an influence on the isospin asymmetry of the other clusters and fragments that is of the same order of magnitude as the influence of the mean field [45,49,50].…”
Section: Discussion and Summarymentioning
confidence: 99%